Synchronous Malignant Otitis Externa and Squamous Cell Carcinoma of the External Auditory Canal - R. Y. Chin; T. B. V. Nguyen (Case Reports in Otolaryngology)
Objectives. To discuss the management of a squamous cell carcinoma in the presence of malignant otitis externa. Study Design. We present only the third reported case in the literature of a synchronous tumour with malignant otitis externa in the literature. Methods. A case report and review of malignant otitis externa and squamous cell carcinomas of the external auditory canal are discussed. Results. A 66-year-old female is presented here with a 2-month history of a painful, discharging left ear refractory to standard antibiotic therapy. Computerised tomography, magnetic resonance imaging, technetium 99 m, and gallium citrate Ga67 scans were consistent with malignant otitis externa. Biopsy in the operating theatre revealed a synchronous squamous cell carcinoma of the external auditory canal. Primary resection of the tumour and surrounding tissues was performed with concomitant treatment with intravenous antibiotics. Conclusions. This is only the third case to be reported in the literature and highlights several important diagnostic and management issues of these two rare conditions. Both conditions may present in a similar manner on clinical assessment and radiological investigations. Aggressive management with surgical resection and treatment with appropriate intravenous antibiotics is necessary to give the best chance for cure.